Dermatitis herpetiformis: jejunal findings and skin response to gluten free diet. - Reunala, T (1984)
Fifty seven children with dermatitis herpetiformis, 18 from Finland and 39 from Hungary, were studied. Diagnostic criteria included the finding of granular IgA deposits in the skin of all patients. The mean age at onset of the rash was 7 X 2 years and favoured sites were the elbows, knees, and buttocks. Symptoms suggesting small intestinal disease were rare but in 35 (61%) of the children subtotal villous atrophy and in 16 (28%) partial villous atrophy were found on jejunal biopsy. Eighteen children underwent a second biopsy after a mean of 21 months on a gluten free diet; villous height was found to be increased and the intraepithelial lymphocyte count decreased in all these patients. Gluten challenge caused a reversal in the two children who underwent a third biopsy. The effect of the gluten free diet on the rash was examined in Finnish children by observing the daily requirements of dapsone, a drug used to control the rash at the beginning of the diet. Eight (67%) of the 12 children were able to stop taking dapsone after a mean of 11 months on the diet and all three patients treated with diet alone became asymptomatic after three to 6 months on the diet. These results confirm that most children with dermatitis herpetiformis have jejunal villous atrophy, though they rarely have gastrointestinal symptoms. The central role of gluten in childhood dermatitis herpetiformis is evidenced by the fact that a gluten free diet helps the damaged jejunal mucosa to recover and controls the rash even in those children who do not have an abnormal jejunal biopsy.